2019
DOI: 10.1016/j.jamda.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic Hypotension and Falls in Older Adults: A Systematic Review and Meta-analysis

Abstract: Objectives: Orthostatic hypotension is a potential risk factor for falls in older adults, but existing evidence on this relationship is inconclusive. This study addresses the association between orthostatic hypotension and falls. Design: Systematic review and meta-analysis of the cross-sectional and longitudinal studies assessing the association between orthostatic hypotension and falls, as preregistered in the PROSPERO database (CRD42017060134). Setting and participants: A literature search was performed on F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 73 publications
2
81
1
7
Order By: Relevance
“…In other studies of SGLT2 inhibitors, volume depletion has been shown to be more frequent in elderly patients [24,37]. The associated risks of volume depletion, particularly in the elderly who are more susceptible to postural hypotension effects such as falls [38], highlight the need to consider this ADR in routine clinical practice.…”
Section: Discussionmentioning
confidence: 98%
“…In other studies of SGLT2 inhibitors, volume depletion has been shown to be more frequent in elderly patients [24,37]. The associated risks of volume depletion, particularly in the elderly who are more susceptible to postural hypotension effects such as falls [38], highlight the need to consider this ADR in routine clinical practice.…”
Section: Discussionmentioning
confidence: 98%
“…* Data on risk factors were obtained from meta-analyses of observational studies. [8][9][10][11][12][13][14][15][16] The limitations of these data include considerable heterogeneity across studies in their definitions of risk factors for falls and evidence of publication bias in some cases. Also, the odds ratio is known to overestimate the relative risk when the outcome of interest is common (as in the case of falls).…”
Section: Prevention Of Falls In Community-dwelling Older Adultsmentioning
confidence: 99%
“…Orthostatic hypotension was diagnosed with a decrease in SBP ≥ 20 mm and/or a decrease in diastolic pressure ≥ 10 mm within 3 minutes after moving to a vertical position (standing position) from the supine position. 13…”
Section: Frailtymentioning
confidence: 99%